Pengaruh Manajemen Puskesmas Terhadap Mutu Pelayanan Puskesmas Kahean Pematangsiantar - Yunardi Yunardi; Sondang Sidabutar; Mei Karo Karo; Trio Ernala Manik (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to analyze the influence of Public Health Center (Puskesmas) management on improving the quality of health services. The main focus of this research is to examine how the implementation of effective management can enhance public access to quality health services. The research method used is descriptive with a qualitative approach, utilizing data collected from various literature sources, journals, and official regulations issued by the Ministry of Health of the Republic of Indonesia. The results show that the application of management principles such as planning, implementation, supervision, and service evaluation significantly contributes to the improvement of service quality. Public Health Centers that implement good management systems tend to demonstrate better staff performance, higher patient satisfaction, and greater effectiveness in public service delivery. Furthermore, government policies such as Minister of Health Regulation No. 75 of 2014 and No. 44 of 2016 serve as important guidelines in achieving standardized and accredited health services. In conclusion, effective management in Public Health Centers plays a crucial role in supporting the development of quality, efficient, and sustainable health services.